Stepped chutes lined with wedge-shaped concrete blocks: hydrodynamic pressures on blocks and stability analysis - Relvas, António T; Pinheiro, António N (Canadian journal of civil engineering, 2011)
The use of wedge-shaped concrete block overlays to protect embankments subject to flows with relatively high velocities is an idea dating from the late 1960s. Subsequent studies addressed the block stability and design, with or without drainage layer underneath, and the flow characteristics. One aspect still lacking systematic research is the block stability considering the influence of the drainage layer and of the uplift pressure beneath the blocks. The stability of blocks located in the training walls of a trapezoidal cross section has never been investigated, although this type of section is expected when installing a concrete block overlay over embankments. The present study addresses this aspect, using a relatively large facility where the blocks are laid on a drainage layer over an embankment artificially saturated, thus intending to simulate a concrete block spillway installed over a compacted homogeneous earth dam. Data collected both in a trapezoidal flume and in a rectangular flume are is analyzed, together with other authors' data for this type of stepped overlay. The inherent hydrodynamic stability is verified. Experiments with hydraulic jump formation over the blocks at the end of the flume also showed block stability.